Modern communications jamming principles and techniques - Poisel, Richard (Artech House, 2011)
This newly revised and greatly expanded edition of the popular Artech House book, Modern Communications Jamming Principles and Techniques, provides an up-to-date, exhaustive treatment of the techniques and methods available to create countermeasures against anti-jam, over-the-air communications. The Second Edition features a wealth of new material on urban warfare, including a computer simulation of EW architecture alternatives for land-based forces based on urban constraints. The new edition also includes an expanded section on time-hopped spread spectrum communications, more details on modern communication system technologies such as CDMA and OFDM, and an in-depth discussion on sources of urban noise. This practical resource is focused on showing you how to design and build jammers specifically targeted at spread spectrum, anti-jam communications. Moreover, you find assistance in evaluating the expected performance of jamming systems against modern communications systems, and discover the best waveform to use to counter communication systems designed to be effective in jamming environments. While mathematical derivations in general are avoided, the book presents error rate performance equations for most modern digital anti-jam communication systems. Written with the professional engineer in mind, this cutting-edge book also serves as an excellent reference for technical personnel new to the communication electronic warfare field due to the inclusion of easy-to-understand introductory material. This resource is packed with over 580 equations and more than 320 illustrations, including graphical examples that allow you to estimate general jammer performance at a glance. Publisher abstract.
Keywords: Radar -- Interference.; Radio -- Interference.; Military telecommunication.; Electronics in military engineering.; Information warfare.; elektronické knihy; electronic books